1973
DOI: 10.1017/s0033291700049655
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in England and Wales 1959–63 Part 1. The county boroughs

Abstract: SYNOPSISA five-year sample of suicide deaths in 82 county boroughs in England and Wales has been examined according to the age and sex of the victims. A number of demographic and other factors were chosen to test out the hypothesis that male suicides were more likely to be associated with other forms of violent death in the community and that female suicides would correlate with a number of variables measuring aspects of sociosexual life. In old age it was postulated that mental and physical illness would outw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…With specific relation to sex differences, he noted that male suicides were particularly connected with loneliness and isolation, especially in old age, and that males who were vulnerable to suicide appeared also to express themselves in other violent ways. 175 These key factors were to be developed in more recent debates about the different ways in which men and women express distress. However, Whitlock acknowledged that, at that time, existing research could say very little about the mental health of communities or about the prevalence of mental illness and alcoholism -which, as will be demonstrated in Chapter 3, were closely correlated.…”
Section: Reflectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…With specific relation to sex differences, he noted that male suicides were particularly connected with loneliness and isolation, especially in old age, and that males who were vulnerable to suicide appeared also to express themselves in other violent ways. 175 These key factors were to be developed in more recent debates about the different ways in which men and women express distress. However, Whitlock acknowledged that, at that time, existing research could say very little about the mental health of communities or about the prevalence of mental illness and alcoholism -which, as will be demonstrated in Chapter 3, were closely correlated.…”
Section: Reflectionsmentioning
confidence: 99%
“…Summing up, he concluded that 'any attempt to bracket together the epidemiological findings in male and female suicide will scarcely do justice to the complexity of circumstances that vary according to the age and sex of the patient'. 176 Psychiatrists and physicians were keen to find ways of preventing suicide by investigating whether those who had succeeded had made earlier attempts and by examining whether or not individuals had been under medical care at the time of their death. Once again, views differed between studies.…”
Section: Reflectionsmentioning
confidence: 99%